Waterlogging tolerance of crops: breeding, mechanism of tolerance, molecular approaches, and future prospects - Ahmed, Fahim; Yusop, Mohd Rafii; Ismail, Mohd Razi; Juraimi, Abdul Shukor; Harun, Abdul Rahim; Ramli, Asfaliza; Latif, Mohammad Abdul (Hindawi Publishing Corporation, 2013)
Submergence or flood is one of the major harmful abiotic stresses in the low-lying countries and crop losses due to waterlogging are considerably high. Plant breeding techniques, conventional or genetic engineering, might be an effective and economic way of developing crops to grow successfully in waterlogged condition. Marker assisted selection (MAS) is a new and more effective approach which can identify genomic regions of crops under stress, which could not be done previously. The discovery of comprehensive molecular linkage maps enables us to do the pyramiding of desirable traits to improve in submergence tolerance through MAS. However, because of genetic and environmental interaction, too many genes encoding a trait, and using undesirable populations the mapping of QTL was hampered to ensure proper growth and yield under waterlogged conditions Steady advances in the field of genomics and proteomics over the years will be helpful to increase the breeding programs which will help to accomplish a significant progress in the field crop variety development and also improvement in near future. Waterlogging response of soybean and major cereal crops, as rice, wheat, barley, and maize and discovery of QTL related with tolerance of waterlogging, development of resistant variety, and, in addition, future prospects have also been discussed.